Development of Android-Based Simple Learning Media Solar System Materials As A Resource of Self-Learning Students of Junior High School - Laili, Ummiy Fauziyah; Wulandari, Ratna Wahyu; Rahmawati, Lailatul (Proceeding International Conference on Education, 2023)
In line with the rapid development of information and communication technology and globalization in the 21st century, reforms are needed in the world of education as a source of needs. The success of a nation is often based on progress and development in the world of education. One of the contributions of technology in the world of education is to make it easier for teachers to establish good communication with students or with students' parents. The existence of learning media is able to concretize concepts and ideas and is able to foster learning motivation in students. The learning resources that will be tested are in the form of materials and programs, namely by developing a simple android application Solar System. Validation was obtained with the "Very Eligible" category for each aspect in the form of a questionnaire filling instrument by lecturers of the Faculty of Tarbiyah at the IAIN Kediri.